2013
DOI: 10.1016/j.eats.2013.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Reduction of a Chronically Dislocated Reversed Shoulder Arthroplasty

Abstract: We present the case of a 64-year-old female patient who had a traumatic dislocation of a reversed shoulder arthroplasty that was unnoticed for 5 weeks and that was reduced arthroscopically. Arthroscopy of the shoulder, as in other joints with prostheses, can facilitate the treatment of conditions that would otherwise require the use of open surgery to solve them and that might become more frequent because of the widespread use of reversed shoulder arthroplasties, which have a high rate of dislocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The first Technical Note related to therapeutic use of arthroscopy on RSA showed that the technique could facilitate the reduction of chronically dislocated shoulder prosthesis, thus avoiding open surgery. 4 The technique here described is useful to better analyze prosthetic joint low-grade infection and to procure multiple tissue samples at the boneeimplant interfaces. This approach can be useful considering that infection could be present although clinical signs and laboratory tests are negative.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first Technical Note related to therapeutic use of arthroscopy on RSA showed that the technique could facilitate the reduction of chronically dislocated shoulder prosthesis, thus avoiding open surgery. 4 The technique here described is useful to better analyze prosthetic joint low-grade infection and to procure multiple tissue samples at the boneeimplant interfaces. This approach can be useful considering that infection could be present although clinical signs and laboratory tests are negative.…”
Section: Discussionmentioning
confidence: 99%
“…The first Technical Note related to therapeutic use of arthroscopy on RSA showed that the technique could facilitate the reduction of chronically dislocated shoulder prosthesis, thus avoiding open surgery. 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation